2017
DOI: 10.1186/s12942-017-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Is gentrification all bad? Positive association between gentrification and individual’s perceived neighborhood collective efficacy in Montreal, Canada

Abstract: BackgroundCollective efficacy has been associated with many health benefits at the neighborhood level. Therefore, understanding why some communities have greater collective efficacy than others is important from a public health perspective. This study examined the relationship between gentrification and collective efficacy, in Montreal Canada.MethodsA gentrification index was created using tract level median household income, proportion of the population with a bachelor’s degree, average rent, proportion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 42 publications
4
34
1
Order By: Relevance
“…An important limitation of previous research was that few of these studies examined the importance of gentrification for health. While there is much concern surrounding gentrification’s role in the deepening social and economic gulf found in cities, existing research has been divided as for how gentrification relates to health in cities [ 4 , 5 , 7 , 8 ]. Findings of the current study indicate residents of neighborhoods experiencing gentrification reported overall better physical health outcomes than those living in neighborhoods that had not experienced gentrification, regardless of its stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important limitation of previous research was that few of these studies examined the importance of gentrification for health. While there is much concern surrounding gentrification’s role in the deepening social and economic gulf found in cities, existing research has been divided as for how gentrification relates to health in cities [ 4 , 5 , 7 , 8 ]. Findings of the current study indicate residents of neighborhoods experiencing gentrification reported overall better physical health outcomes than those living in neighborhoods that had not experienced gentrification, regardless of its stage.…”
Section: Discussionmentioning
confidence: 99%
“…These findings stand out for their robustness. All of the previous research on gentrification and health was limited to case studies of specific cities, namely Montreal [ 8 ], New York City [ 5 ], Philadelphia [ 4 ], and metropolitan areas in California [ 6 ]. While each of these studies analyzed variation in health outcomes with large samples of neighborhoods, all were potentially limited in their generalizability because they focused on at most a few large cities or regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined gentrifying and non-gentrifying neighborhoods in NYC, based in part on variables used in other studies [ 9 , 10 ]. We obtained single-year estimates of median household income, median rental price, and proportion of adults aged ≥25 years with a college degree for each NYC neighborhood from 2005–2014 ACS data.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies were conducted in the United States . A handful of studies were conducted in Spain, Australia, and Canada [5,28,[41][42][43][44][45][46][47][48][49]. Of the 36 papers included in this literature review, 6 were qualitative, 24 were quantitative, and 3 were review papers.…”
Section: Overviewmentioning
confidence: 99%